2006
DOI: 10.1002/polb.21015
|View full text |Cite
|
Sign up to set email alerts
|

Melting of solvents nanoconfined by polymers and networks

Abstract: Thermoporosimetry is becoming increasingly used to study nanoscale heterogeneity and structure in polymer networks. The starting point for thermoporosimetry is the Gibbs-Thomson (GT) relation between melting point and inverse crystal size. In the case of polymers, the Flory-Huggins (FH) model also predicts that there is a depression of the melting point because of the mixing of the polymer and the solvent molecules, and this needs to be taken into account. The first step in analysis of size heterogeneity using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 34 publications
0
25
0
2
Order By: Relevance
“…This experiment is based on the fact that solvent molecules constrained to small volumes form only relatively small crystallites upon crystallization and therefore exhibit lower crystallization temperatures [25]. Broad distributions of cavity sizes should give rise to broad distributions of crystallites sizes and thus crystallites melting points [26]. Therefore, differential scanning calorimetry measurements performed on swollen sample with solvent molecules constrained in the pores can give evidence of several crystallization temperatures, which are indicative of the pore sizes and of the distributions of these sizes.…”
Section: Thermoporosimetrymentioning
confidence: 99%
“…This experiment is based on the fact that solvent molecules constrained to small volumes form only relatively small crystallites upon crystallization and therefore exhibit lower crystallization temperatures [25]. Broad distributions of cavity sizes should give rise to broad distributions of crystallites sizes and thus crystallites melting points [26]. Therefore, differential scanning calorimetry measurements performed on swollen sample with solvent molecules constrained in the pores can give evidence of several crystallization temperatures, which are indicative of the pore sizes and of the distributions of these sizes.…”
Section: Thermoporosimetrymentioning
confidence: 99%
“…24,25 In addition to the plasticization and potential polymersolvent interaction effects, more complications can arise because small size has been observed to decrease the heat of fusion of organic liquids confined in nanopores. 23 As a continuation to previous work from Texas Tech, 10 the present work further explores the validity of the FH model prediction and the method of thermoporosimetry. Differential scanning calorimetry (DSC) is used to characterize the melting behavior of cyclohexane and cyclooctane in poly (dimethyl siloxane) (PDMS) precursors and model networks.…”
Section: Introductionmentioning
confidence: 84%
“…The magnitude of the melting point depression for cyclohexane in the PDMS precursors varies from 0 to 70 C, which is much larger than what is observed for many other systems, such as benzene and hexadecane in polyisoprene or natural rubber. 9,10,20,19 In these systems, the melting point depression of the solvents generally does not exceed 40 C. Honiball et al 20 also examined a number of solvents and found that cyclohexane exhibits large melting point depressions in natural rubber. The heat of fusion decreases almost linearly with the increase of polymer content, as indicated in Figure 3.…”
Section: Melting Behavior Of Cyclohexane In Pdms Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…10. From this plot, the width of the distribution provides an idea of the network homogeneity in terms of molar mass distribution between two crosslinks [29,31,41,49]. Furthermore, the pore size weight average value Rp m can be determined by using Eq.…”
Section: Structural Evolution With Aging Timementioning
confidence: 99%